(untitled) (Journal of Contemporary Educational Policies and Practices, 2025)
Nowadays, technology plays a significant role in education, making it essential for teachers, particularly at the higher education level, to be evaluated on their digital competencies (DCs) to meet the demands of modern teaching and learning. This study employs a mixed-methods approach with survey questionnaires and interviews to examine the DCs and the implementation of digital technologies in the English teaching of 51 English lecturers across different universities in Vietnam based on the digital competencies of Educators (DCE) model. The research results show that the majority of lecturers perceived themselves as possessing a high level of DCs with the highest proficiency in the area of Professional Engagement and the lowest in Assessment. Additionally, there are no significant differences in DCs scores across genders, teaching experience and qualifications. However, in terms of age, younger lecturers demonstrate stronger DCs while those older might need additional support. In practice, the teachers acknowledged that digital tools play a crucial role in modern English teaching, but requires careful consideration, preparation, and adaptability to overcome the challenges and achieve efficiency. The study findings contribute to the ongoing discourse on teachers’ DCs and offer suggestions for educational policymakers, curriculum developers, and teacher training programs to enhance teaching and learning outcomes.